2018
DOI: 10.1124/jpet.118.249409
|View full text |Cite
|
Sign up to set email alerts
|

NYX-2925 Is a Novel N-Methyl-d-Aspartate Receptor Modulator that Induces Rapid and Long-Lasting Analgesia in Rat Models of Neuropathic Pain

Abstract: NYX-2925 [(2S,3R)-3-hydroxy-2-((R)-5-isobutyryl-1-oxo-2,5-diazaspiro[3.4]octan-2-yl)butanamide] is a novel -methyl-d-aspartate (NMDA) receptor modulator that is currently being investigated in phase 2 clinical studies for the treatment of painful diabetic peripheral neuropathy and fibromyalgia. Previous studies demonstrated that NYX-2925 is a member of a novel class of NMDA receptor-specific modulators that affect synaptic plasticity processes associated with learning and memory. Studies here examined NYX-2925… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 77 publications
1
27
0
Order By: Relevance
“…and Khan et al ) via increasing synaptic GluN2B as shown both in vitro (Fig. ) and in vivo (Khan et al ; Ghoreishi‐Haack et al ; Supporting Information). This pharmacokinetic‐based plasticity model (Fig.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…and Khan et al ) via increasing synaptic GluN2B as shown both in vitro (Fig. ) and in vivo (Khan et al ; Ghoreishi‐Haack et al ; Supporting Information). This pharmacokinetic‐based plasticity model (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…). This same dose also facilitated novel object recognition and positive emotional learning (Khan et al ) as well as reduced neuropathic pain in rats (Ghoreishi‐Haack et al ). Thus, mid‐nanomolar NYX‐2925 concentrations facilitate cognition and LTP.…”
Section: Discussionmentioning
confidence: 96%
“…NYX‐2925 has been studied in several animal models of neuropathic pain, including neuropathic pain induced by sciatic nerve ligation and painful diabetic neuropathy‐induced pain with streptozotocin. In the Bennett chronic constriction injury model of neuropathic pain, rats given a single dose of NYX‐2925 at 1–2 weeks post‐sciatic nerve ligation demonstrated analgesia at 1 hour, 24 hours, and 1 week postdrug administration . Similar rapid (1 hour) and long‐lasting (1 week) analgesia was observed in the rat model of streptozotocin‐induced painful diabetic neuropathy .…”
mentioning
confidence: 55%
“…In the Bennett chronic constriction injury model of neuropathic pain, rats given a single dose of NYX‐2925 at 1–2 weeks post‐sciatic nerve ligation demonstrated analgesia at 1 hour, 24 hours, and 1 week postdrug administration . Similar rapid (1 hour) and long‐lasting (1 week) analgesia was observed in the rat model of streptozotocin‐induced painful diabetic neuropathy . NYX‐2925 modulates NMDARs in a highly specific and selective manner to enhance synaptic plasticity, which is a probable mechanism for the long‐duration effects seen in these pain models.…”
mentioning
confidence: 71%
See 1 more Smart Citation